The effect of Universities and University Colleges Act 1971 & Education Institution (Discipline) Act 1976 towards today’s undergraduates / Ariff Firman Mohd Sidek … [et al.] - Mohd Sidek, Ariff Firman; Anyie, Clarie Uring; Kenny, Glen; Ahmad, Mohamad Tarmizi (2005)
As a most rapidly developing third world country, we should posses credible and charismatic young generation to achieve our vision and mission. The human capital is an important component in the vision which has been laid down by YAB Dato' Seri Abdullah Ahmad Badawi, Prime Minister of Malaysia. This research is based on the Universities and University Colleges Act 1971 and Education Institutions (Discipline) 1976 which supervise the activities of the undergraduates in public universities. Both the Acts provide the limitations of freedom of speech and expression in Malaysia towards undergraduates which has been granted by the Federal Constitution. Nowadays, many parties outside the universities always blamed our graduates to be lacking of certain requirement and skills needed by the various sectors in the economic development of the country. The research deals with the effect of the implementation of both the acts towards undergraduates. We also take the initiative to conduct it especially for the benefit of undergraduates, community at large, country and also our future generation. The aim of this research is to clarify and determine the effect of the implementation of both the Acts from the undergraduates and academician perspectives. We also provide some suggestions and recommendations for the government to enhance the situation in the universities which can increase the value of human capital.